Becoming International: Are Malaysian ArchitecturalFirms Ready to Take the Challenges? - Ahmad, S.Z.; Kitchen, P.J.; Shaharudin, R.S.; Kamarulzaman, Y. (Zia World Press, Australia, Australia, 2008)
Malaysian architectural firms are being increasingly encouraged to internationalise their business operations due to market liberalization factors but they are often perceived to lack expertise in terms of internationalisation. This paper presents the outcomes of an empirical investigation to explore and identify characteristics that Malaysian architectural firms need in order to compete internationally. Empirically data were obtained from a survey of 56 architectural firms registered with the Board of Architects Malaysia (BAM) ranging from sole proprietorships, partnerships and corporate bodies. To obtain a better understanding of this dynamic issue, depth interviews were also conducted with senior managers from a sample of 25 firms. The findings indicate that although management realise the importance of an international presence, this has not necessarily been translated into direct investment yet. Key impediments and barriers are the small size of architectural firms, perceived risks involved in expanding abroad, limited international exposure, and lack of international contacts. Meanwhile, despite the trend of market liberalisation, business opportunities are being lost. An agenda for managerial action is suggested.